John and Elaine Steinbeck in Hungary. - Keleti Eva:::Creator::::::::::::
John and Elaine Steinbeck in Budapest, Hungary. Photograph taken by Keleti Eva of the Magyar Tavirati Iroda (Magyar Telegraph), Photo Division